(untitled) (Journal of Pakistan Orthopaedic Association, 2015)
Introduction: Bicondylar fractures create a challenging situation to the surgeon as any attempt of open reduction and internal fixation may jeopardize the delicate soft tissue in the region and different techniques have been applied. The ideal management of such fracture however, remains controversial. The purposes of this study was to evaluate the radiological and functional outcome of an alternate surgical technique in which one third tubular plate is used along with a single T buttress plate or 6.5 mm cancellous screws in the management of bicondylar tibial plateau fractures. Application of this low profile plate over the posteromedial cortex to serve antiglide purpose needs less soft tissue dissection and therefore it was hypothesized that lesser complications and better functional outcome may be achieved. Meterials and Methods: A descriptive case series was conducted from July 2011 to July 2013. 24 (18 male and 6 females) patients, mean age 34, with bicondylar fractures presenting in the Accident and Emergency department were operated. In all the cases posteromedial cortex was anatomically reduced and stabilized with 1/3rd tubular plate as the first step of the procedure, directly approaching the posteromedial cortex. It was followed by reduction of the lateral condyle and fixation with buttress plate or cancellous lag screws, depending on the situation. Patients were followed up on 1st, 3rd 6th and 12th postoperative week. Radiographs were obtained to assess the integrity of articular surface and complications regarding surgery were assessed. Articular subsidence of more than 5mm was considered as failure of articular surface integrity. Presence of infection, deep vein thrombosis, arthrofibrosis, wound dehiscence and exposed implants were regarded as complications of internal fixation. Results: Out of 24 patients 21 patients completed the follow-up program and were included in the study. In all 21 patients articular surface remained intact till the final follow up. 4 patients has complications which included infection in one case and arthrofibrosis in three. Conclusion: Addressing the posteromedial column of the proximal tibia in bicondylar tibial plateau fractures with 1/3rd tubular plate produces very good outcome regarding maintenance of the articular surface and lesser soft tissue complications.